Data based individualization in early writing: the importance and measurement of implementation fidelity - Lembke, Erica S.; McMaster, Kristen L.; Duesenberg-Marshall, McKinzie D.; McCollom, Elizabeth; Choi, Seohyeon; Shanahan, Emma; An, Jechun; Sussman-Dawson, Katya; Birinci, Seyma (Frontiers in Education, 2024)
In this paper we describe the process of monitoring fidelity of implementation for a teacherimplemented early writing intervention. As part of a large, federally funded project, teachers who worked with students in grades 1 through 3 in schools across two states in the US were recruited and then randomly assigned to implementation and control conditions. Using Data-Based Individualization (DBI) as a framework for best practice in assessment and intervention, teachers in the implementation group received professional development on early writing intervention and assessment and then implemented these practices with their students who had significant writing challenges. Coaches, who were part of the research project, supported teachers and also observed teachers in both the implementation and control conditions at least twice during the course of the 20-week study. This paper focuses on the results of the fidelity measures that were administered throughout the project. An overview of the importance of fidelity checks is followed by a description of the fidelity tools used, as well as data from those tools. Areas of strength and challenge for teachers when implementing early writing assessment and intervention and engaging in data-based decision making with fidelity are discussed, along with recommendations regarding the practical and research importance of fidelity checks.